Conspiracy beliefs and negative attitudes towards outgroups in times of crises: Experimental evidence from Germany. - Rebecca Endtricht; Eylem Kanol (PLoS ONE, 2024)
While research on the determinants of conspiracy beliefs has been growing, there is still limited attention given to the broader consequences of conspiracy theories. This study examines the effects of conspiratorial framing on outgroup evaluations in the context of societal crises. Using an experimental design and a large representative sample of the German population, we exposed participants to conspiratorial framings of health, economic, and security crisis scenarios. The findings reveal that exposure to conspiratorial framing of crises leads to significantly more negative attitudes towards outgroups compared to control conditions. The impact is most pronounced in the security crisis treatment condition, particularly in war scenarios. Additionally, our study demonstrates the important role of political ideology, as individuals with left- as well as right-wing ideologies displayed more negative attitudes towards outgroups when exposed to conspiratorial framings of crises. These findings contribute to the literature by providing experimental evidence of the detrimental effects of conspiracy narratives on intergroup attitudes during crises.